Assessing the nexus among energy consumption, foreign direct investment and economic growth in sub-Saharan Africa - Iyabo Adeola Olanrele; Segun S. Awode (CBN Journal of Applied Statistics, 2022)
This study examines the dynamic relationship among energy consumption, foreign direct investment, and economic growth in Sub-Sahara Africa. Beyond assessing the tripartite causal relationship, the study investigates the extent of impacts among energy consumption, foreign direct investment, and economic growth using the Gen- eralised Method of Moments. The study utilises data from 42 Sub-Saharan African countries spanning 1991 to 2018. Findings from the study show that a percentage increase in energy consumption engenders economic growth by 1.3 percent. Con- versely, economic growth increases energy consumption by 0.004 percent. Also, there is a significant one-way causality running from foreign direct investment (FDI) to economic growth. The link between energy consumption and FDI were not sta- tistically significant in both directions. The study advocates that government in Sub-Saharan Africa should ensure more energy access to enhance economic growth.
Keywords: O13; O47; 330; Economic growth; energy consumption; foreign direct investment; Sub- Saharan Africa